TO PROBLEM OF DESTRUCTION OF DEFORMABLE MEDIA. 2. DISCUSSING THE RESULTS OF ANALYTIC SOLUTIONS - Chanyshev A.I. (My University, 2001)
Problems of destruction of deformable media have been solved. Mathematical models have been used during solving the problems. Differential equations of hyperbolic type have been applied in the models. The case of rock mass around cylindrical mine working has been considered. It has been shown that in theory of destruction includes problems which are similar to those of plasticity theory. Construction of the determining relations has been discussed. Methods of investigating the mode of strength loss in destruction surface have been shown. Variation of hydrostatic and maximal tangential stresses have been analyzed. Position of the main axes of stress tensor has been discussed.